ATSA ARCHITECTS DIRECTOR SHARES CHALLENGES IN ARCHITECTURE AND INTERIOR DESIGN PRACTICE WITH HBP STUDENTS - MPRC, Pusat Media & Perhubungan Awam (2017)
USM, PENANG, 2 March 2017 The School of Housing, Building and Planning (HBP) Universiti Sains Malaysia (USM), more specifically the Design Cluster, was delighted to have a courtesy visit from Ar. Azim Tan Sri A. Aziz recently, to present a talk relating to his profession to approximately 220 architecture and interior design students entitled “Challenges in the Architecture and Interior Design Practice in Malaysia”.